Clinicopathological spectrum of cutaneous malignancies at the skin tumour clinic, charlotte Maxeke Johannesburg academic hospital in Johannesburg, South Africa: a 5-year retrospective review - Gwinji, Tapiwa Munyaradzi (University of the Witwatersrand, Johannesburg, 2023)
Background Skin cancer is the most common malignancy in South Africa, incidence of which continues to rise. This disease remains a consistent problem in South Africa due to a multifactorial risk complex arising mainly from the high levels of year-round Ultraviolet (UV) exposure, high burden of HIV and late health seeking behaviour leading to poly-etiological skin cancers. Despite the ever-present danger that is cancer, the data and literature surrounding skin cancers among different races and ethnic groups remains inadequate as there are few population-based cancer registries in South Africa and only histologically confirmed cancers are logged into the national cancer registry. Objectives To describe the nature, extent and demographic characteristics of patients with histologically confirmed skin cancer seen at the Charlotte Maxeke Johannesburg Academic Hospital (CMJAH) multidisciplinary skin cancer clinic during the period of January 2015 to December 2019 and to add to the body of literature concerning skin cancers in South Africa. Methods A retrospective chart review identified all patients who were managed for histologically confirmed malignant skin tumours at CMJAH skin tumour clinic. Types, quantity and distribution of common invasive malignancies by population group, age, gender, anatomical site and risk factor were explored. Result A total number of 531 participants with histologically confirmed skin cancers were identified. The most common malignancies were Kaposi’s sarcoma(KS) (53.2%), squamous cell carcinoma (SCC) (27.0%), basal cell carcinoma (BCC) (10.4%), cutaneous melanoma (CM) (7.4%) and mycosis fungoides (MF) (4.2%). SCC and AIDS-associated KS were the most common skin cancer in the white and black population respectively. Conclusion This study provides valuable scientific data on the distribution and patient demographics of skin cancer in the public health system in Johannesburg, South Africa, on which further research can be based. This study highlights the burden of HIV associated skin cancer in this region. There is a need for further research and equitable appropriation of resources and public health awareness efforts towards strengthening UV and HIV-related skin cancer prevention initiatives in SA.
A research report (in the format of a “submissible” paper) submitted in partial fulfillment of the requirements for the degree of Master of Medicine (Dermatology) to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, July 2023
Keywords: Skin cancer; South Africa; Ultraviolet (UV); HIV; UCTD; SDG-3: Good health and well-being